A Revision to the Theory and the Practice of Development Accounting (2014)
Practitioners of development accounting assume that the private return on schooling equals its social marginal product. I show that this assumption is inconsistent with the mathematical structure of a multiplicative production function, which specifies that the private return is only a fraction of the social marginal product. I then show that the empirical results from development accounting in the literature substantially underestimate human capital’s contribution to national output and overestimate national productivity differences.